Volume 2A: Turbomachinery 2015
DOI: 10.1115/gt2015-43173
|View full text |Cite
|
Sign up to set email alerts
|

Variable Geometry Design of a High Endwall Angle Power Turbine for Marine Gas Turbines

Abstract: Variable geometry turbines are widely used to improve the part-load performance of gas turbine engines. However, there is a performance penalty associated with the vane-end clearance required for the movement of variable vanes. Especially for variable geometry turbines with high casing-endwall angles, greater vane-end clearances are necessary due to annulus slope, and then high endwall leakages would occur, which further deteriorates turbine efficiency. The variable geometry design of the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…高杰等人 [33] 提出台阶型球面端壁概念, 结合倾斜 轴式可调静叶结构, 以期解决大扩张角端壁可调静叶 转动时间隙变化剧烈的问题; 同时, 哈尔滨工程大学 刘鹏飞等人 [44] 进一步提出旨在减小整周可调静叶总间 隙泄漏面积的三维设计概念, 以期解决该类可调静叶 端部间隙及泄漏损失较大的问题, 初步的单级及多级 变几何涡轮设计结果证实了上述设计思想的有效性.…”
Section: 可调静叶端区流场特性unclassified
“…高杰等人 [33] 提出台阶型球面端壁概念, 结合倾斜 轴式可调静叶结构, 以期解决大扩张角端壁可调静叶 转动时间隙变化剧烈的问题; 同时, 哈尔滨工程大学 刘鹏飞等人 [44] 进一步提出旨在减小整周可调静叶总间 隙泄漏面积的三维设计概念, 以期解决该类可调静叶 端部间隙及泄漏损失较大的问题, 初步的单级及多级 变几何涡轮设计结果证实了上述设计思想的有效性.…”
Section: 可调静叶端区流场特性unclassified
“…It is worth noting that a low-speed cascade is used here, since the real exit Mach number of a variable geometry turbine is about 0.44, and the Mach number effects are relatively weak. In addition, if interested, the readers can refer to the authors' previous research work 9 to understand the variable geometry effects in a real machine.…”
Section: Experimental Conditions and Uncertaintiesmentioning
confidence: 99%
“…The results indicated that the efficiency in the spherical endwall case is reduced when the setting angle deviates from 0 ; however, the efficiency in the cylindrical endwall case achieves its maximum value when the vane setting angle is located at about À5 . Gao et al 9 preliminarily redesigned the first stage of a high endwall slope angle power turbine to incorporate variable vanes by proposed stepped spherical endwall concept. The results showed that the efficiency of the new-designed variable geometry power turbine keeps nearly unchanged as compared to the fixed geometry turbine.…”
Section: Introductionmentioning
confidence: 99%
“…In a high endwall-angle variable geometry turbine, when the variable vane rotates, the vane tip clearance becomes non-uniform (Gao et al 9 ); and there are several pits or protrusions formed near the adjustable pivot ends, which lead to a serious deterioration of endwall flow fields. Based on the above analyses, due to the special structure of a CWT design, it can be applied to the variable vane ends, in order both to overcome this structural problem and to reduce the performance sensitivity to vane tip clearance height.…”
Section: Sensitivity To Vane Tip Clearance Heightmentioning
confidence: 99%
“…The studies indicated that the endwall flow pattern of variable vanes is different from that of fixed vanes, and there are flow interactions between leakage and passage vortices, causing extra losses. Gao et al 9 redesigned the high endwall-angle first-stage turbine with the incorporation of variable vanes by the proposed concept of stepped spherical endwall. The computed results indicated that the design point efficiency of the new designed variable turbine keeps constant nearly as compared with the fixed geometry turbine.…”
Section: Introductionmentioning
confidence: 99%